Effects of varying longitudinal bending stiffness in running shoes on lower limb biomechanics of elite marathon runners - Yang, H.; Cai, Y.; Li, K.; Wang, X.; Liu, T. (Frontiers in Sports and Active Living, 2025)
Objective: This study examined the effect of three levels of longitudinal bending stiffness (LBS) in carbon-plated shoes on lower limb biomechanics.